Green Tourism: Management Practices for Sustainable Tourism in the First District of Albay - Barbacena, Grace Ann R.; Boragay, Tonie Rose B.; Bron, Jhoanna Ryza O.; Potonia, Shaira Joy C.; Engay, Federico B.; Martirez, Katherine C. (International Journal of Research in Interdisciplinary Studies, 2025)
Sustainability systems are market-based tools designed to address the most pressing social and environmental challenges of our time. They give people power to make an impact. This study adapted the quantitative research method using the descriptive-survey technique. This is the most appropriate research method and design to be used considering that the data to be collected will use a questionnaire composed of a checklist and a five-point Likert scale, and shall be analyzed statistically involving appropriate statistical tools. Findings revealed that majority of the ecotourism sites in the First District of Albay are privately owned and operating for almost eleven (11) years and as to the type of ecotourism site majority are cultural and with an approximate annual revenue of P50,000 to P100,000. Moreover, the ecotourism site owners are more aware of the employment opportunities that they can offer to the community like hotel housekeeper and resort manager. The top two sustainable tourism strategies employed by the ecotourism sites are the provision of eco-friendly environment and protection of natural resources. The top two challenges met by the ecotourism owners are the exploitation of natural resources and policy and regulatory challenges.